Sustainable expert virtual machine migration in dynamic clouds. (September 2022) - Seddiki, Doraid; Galán, Sebastián García; Expósito, J. Enrique Muñoz; Ibañez, Manuel Valverde; Marciniak, Tomasz; -Pérez de Prado, Rocío J.
Abstract: Operation on demand flexibility in cloud computing services has resulted in great popularity and wide adoption. These services integrate thousands of computers, storage and communication networks, which implies a high consumption of electrical energy. Therefore, renewable energy-based cloud data centers are replacing traditional energy power grids. In this regard, the workload could be transferred to different nodes among different cloud data centers geographically distributed regarding renewable energy availability. In this sense, this paper presents a framework based on Cloudsim for virtual machine migrations among cloud data centers regarding sustainability optimization. Moreover, an approach for migrations among datacenters based on an expert system has been tested in several scenarios with renewable energy dynamically available. Experimental results show the improvements of the proposed framework and how expert systems can take advantage of renewable energy availability in terms of sustainability while preserving the QoS in terms of execution time. Graphical Abstract: Image, graphical abstract